Cándido María Trigueros’ version of the Theocritus’ Idyll XIX in the Bucolic and Anacreontic Tradition of the 18th Century - Jesús M.ª NIETO IBÁÑEZ (Cuadernos Dieciochistas)
Edition and study of the Theocritus» Idyll XIX, Love, the Beehive Thief, whose text was transcribed in Greek and translated to Latin and to Spanish by Candido María Trigueros. In addition to analyzing the translating technique of the author, the text is discussed in the tradition of 18th Century Anacreontic poetry and its relationship to other texts translated by Trigueros, such as the Fugitive Love by Moschus, the Anacreontic XXXVand the anonymous composition To Dead Adonis.